Effects Of Electrode Materials On Electrical Properties Of Cacu3ti4o12 At 100 Hz – 1 Ghz - Sulaiman, Muhammad Azwadi (2013)

(untitled)
CaCu3Ti4O12 (CCTO) has attracted much interest because of its extraordinary high dieletric constant of 100,000 at room temperature and very small temperature dependence in a broad temperature range from 100 K to near 400 K. This high dielectric constant offers opportunities in miniaturization of electronic application nowadays. However, CCTO also possesses high dielectric loss which is undesirable in electronic applications. To lower the dielectric loss, it is necessary to understand the origin of polarization responds and relaxation mechanism in CCTO. Using wide frequency impedance spectroscopy (IS) from 100 Hz to 1 GHz, the origins of polarization effect can be revealed. One of the important origins is the used of different electrode materials which determine the contact condition to the bulk CCTO. A research was carried out to study the effect of electrode materials to the electrical properties of CCTO at the frequencies of 100 Hz to 1 GHz. Samples were prepared through solid state reaction methods and starting materials of CaCO3, CuO and TiO2 has been used. After the characterization, the starting materials were mixed for 1 hour and thermal analysis was done. Mixed powder was calcined at 900 to 1000ºC for 3 to 6 hours. Phase analyses and microstructure observation was carried out. Calcination at 1000ºC for 3 hours produced almost single phase of CCTO. The calcined powder was pressed into pellet forms and the sintering processes were done between 1000 to 1050ºC for 3 to 10 hours. X-ray diffraction (XRD) analisys indicated that sintering at 1030ºC and below increased the lattice parameter and long soaking time until 10 hours at 1040ºC has decreased the lattice parameter. Longer soaking times are also increasing the crystallite size and 6 hours of soaking time or xix more produced large grains (>100μm). The IS reported the dielectric constants and dielectric loss are also increased with the sintering soaking time. Relaxation peak at 10 MHz is suggested due to the loss of grain boundaries polarization effects. High frequency curve of impedance complex was observed and modeled as domain and domain boundary contribution in equivalence circuit analyses. The current-voltage characteristic reported the non-linearity and proved the Schottky’s barrier of CCTO. Sample sintered at 1040ºC for 4 hours have stable and high dielectric constant and low dielectric loss over the frequency range. Heat treatment study to the electrode from room temperature to 400ºC in argon gas revealed the increase of dielectric constant with the increasing of treatment temperature. The dielectric constant improvement was due to more Schottkys contact formation after the treatment. Treatment at 300ºC is the most suitable temperature to produce high dielectric constant CCTO with low dielectric loss. Schottky’s effect to the contact were observed by applying different electrode material, gold, platinum, silver and aluminium and non-linear of current-voltage characteristic was revealed on Pt and Au electrode. This is due to both electrodes have higher work function than the other electrodes. Samples with Au electrode showed high dielectric constant at 1 MHz (4,398) and low dielectric loss (0.03 at 1.58 kHz). Wide frequency measurement of the electrical properties shows the responds from grain, grain boundary, domain and domain boundary through impedance complex plane curve fitting method. Their resistivities have changed with the study parameters and high frequency respond associated with domain boundary resistivities has been modelled according the equivalence circuit analysis.